The impact of Trans-Pacific Partnership agreement on the Canadian economy - Kakali Mukhopadhyay; Paul J. Thomassin (Journal of Economic Structures, 2018)
The Trans-Pacific Partnership is the most comprehensive trade agreement in the world. The TPP will help deepen Canada's trade ties in the dynamic and fast growing Asia-Pacific region while strengthening existing economic partnerships with NAFTA partners and across Americas. The TPP will eliminate tariffs on almost all of Canada's key exports and offer access to new opportunities in the Asia-Pacific region. Tariffs and other barriers on a wide range of Canadian products from various sectors will be reduced, including in agriculture and agri-food, fish and seafood, forestry and wood products, metals and mining and industrial goods. These benefits can only be derived if USA ratifies it. However, the US president has already signed a presidential memorandum confirming the US withdrawal from the TPP agreement. With this background, the current study evaluates the economic impacts of the Trans-Pacific Partnership agreements on the Canadian economy by the year 2030 using a global CGE framework. The study undertakes a number of simulations based on the level of tariff reduction across selected commodities between Canada and other TPP Nations. The GTAP 9 Data Base with the reference year of 2011 is used for the study. Results show that Canada stands to benefit significantly from improved access to the TPP region. Canada expects a considerable increase in agricultural export. Canola, processed food and beverages, seafood, beef and pork sectors are expected to benefit from the deal. Industrial goods like farming and construction equipment, metal and mineral, transport equipment, machinery would gain from TPP agreements. The agreement would help increase Canada's manufacturing and exporting output. The banking sector is also expected to benefit from the deal. Additionally, a significant number of skilled and unskilled employment is likely to generate in Canada.
Keywords: 330; Trans-Pacific Partnership agreement; Canada; Global CGE